2018
DOI: 10.1002/admt.201800593
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized Bamboos as Excellent 3D Solar Vapor‐Generation Devices

Abstract: of the 2D structures has approached its limit (< 90%) due to which the energy loss via reflection (2-5%) and thermal radiation heat loss (8-12%) occurs in all the 2D structures.One of the effective strategies for further improving the vapor-generation efficiency is to decrease the surface temperature of the absorber by increasing the surface area within a given projection area. [22] Some unprecedented vapor-generation rates have been reported in various 3D generators, which are all beyond the input solar energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 30 publications
2
93
0
2
Order By: Relevance
“…[ 33 ] Gu and coworkers revealed that bamboo can be an excellent 3D solar vapor‐generation device with an extremely high evaporation rate of 3.13 kg m −2 h −1 under 1 sun irradiation by a three‐step carbonization method, and the bamboo‐based evaporator has the advantages of low‐cost, self‐cleaning, solid durable, and scalable. [ 34 ] In our previous work, the extremely cheap carbonized kelp (≈3.8 $ m −2 ) with good stability, high solar absorption (≈93%), porous microstructure, and hydrophilic surface was found to be efficient for SSG and seawater desalination, an evaporation rate of 1.351 kg m −2 h −1 was attained under 1 sun irradiation. Moreover, a capillarity‐driven interfacial self‐coating method was developed to prepare the super‐hydrophilic photothermal layer based on carbonized towel‐gourd sponges, which exhibited a high evaporation rate of 1.53 kg m −2 h −1 under 1 sun irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Gu and coworkers revealed that bamboo can be an excellent 3D solar vapor‐generation device with an extremely high evaporation rate of 3.13 kg m −2 h −1 under 1 sun irradiation by a three‐step carbonization method, and the bamboo‐based evaporator has the advantages of low‐cost, self‐cleaning, solid durable, and scalable. [ 34 ] In our previous work, the extremely cheap carbonized kelp (≈3.8 $ m −2 ) with good stability, high solar absorption (≈93%), porous microstructure, and hydrophilic surface was found to be efficient for SSG and seawater desalination, an evaporation rate of 1.351 kg m −2 h −1 was attained under 1 sun irradiation. Moreover, a capillarity‐driven interfacial self‐coating method was developed to prepare the super‐hydrophilic photothermal layer based on carbonized towel‐gourd sponges, which exhibited a high evaporation rate of 1.53 kg m −2 h −1 under 1 sun irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced h VCMF has also been found in other literatures, like in hierarchically nanostructured gel, porous cellulose membrane, and carbonized bamboos. The reduction is possibly attributed to the cluster escape mode of water molecules …”
Section: Resultsmentioning
confidence: 99%
“…Natural materials like wood, mushroom, food waste, flour, cotton, daikon, bamboo, etc., after a common thermal treatment, namely carbonization, can obtain excellent light‐absorbing ability, and thus are widely employed in solar evaporation systems. [ 70–79 ] These low‐cost natural materials are of great abundance, which befits future large‐scale applications.…”
Section: Design Principles To Approach 100% Efficiencymentioning
confidence: 99%